Do Embedded and Peripheral Corporate Social Responsibility Activities Lower Employees’ Turnover Intentions? - Liu, Yumin; Ijlal, Kamran; Hanif, Muhammad Shehzad; Khurshid, Aitzaz; Ahmed, Zeeshan (Frontiers in Psychology, 2022)
Corporate Social Responsibility remains a topic of interest for both theory and practice due to its multifaceted avenues and potential for growth. We have chosen Embedded CSR and Peripheral CSR measures to evaluate their relative impact on employee turnover intentions through a mediation mechanism of organizational citizenship behavior (OCB). In doing so, this study addresses important stakeholder concerns and provides meaningful managerial contributions for the employers to encourage more employee participation (through lowering turnover intention) towards sustainable corporate performance. This study incorporates four hypotheses that are tested in a structural equation modeling framework by employing Warp-PLS software. Data was collected from 297 employees working in firms; renowned for their CSR initiatives. We found support for all hypotheses with varying effects leading to strong theoretical contributions for stakeholder theory by addressing the tensions in the theory as well as implications and a deeper understating for managers in initiating Peripheral and Embedded CSR activities for their firms.